We the Peoples. A Rawlsian Perspective of International Justice - Manzano, Juan Antonio Fernández (Journal of Leadership, Accountability and Ethics, 2021)
This text analyses the possibility of discussing global justice today using the theoretical tools of John Rawls. With that end in mind, we will present the main lines of his justice as fairness to see how Rawls extrapolates the fundamental bases of his theory of justice at a global level. Having done that, we will evaluate the theoretical justification of the Rawlsian global approach, its internal consistency and its validity in practice to conclude that the Rawlsian defense of the autonomy of peoples prevents his theory to properly set limits on global inequalities. By replacing the redistributive potential of the domestic difference principle by a meager duty of assistance, Rawls’s theory is quite permissive with global material inequalities, which can be considered an inconsistency.